2021
DOI: 10.1029/2021jd034541
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐Tropospheric Troughs and North American Monsoon Rainfall in a Long‐Term Track Dataset

Abstract: In all monsoon climates, the region of peak seasonal mean precipitation lies on the equatorial side of an upper-level anticyclone. Mid-to upper-level vorticity anomalies that are both carried by and draw energy from this anticyclonic flow have been clearly documented in the South Asian monsoon (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In contrast, the positive PV200 anomalies are relatively smaller for westward-moving UTTs, and they are located in the tropical easterlies. This follows Igel et al (2021), where it is argued that TUTTs are advected by the background easterlies. Moreover, the boundary of westerly and easterly flow moves further north during westward-UTT events.…”
Section: Upper Troposphere Troughsmentioning
confidence: 88%
See 1 more Smart Citation
“…In contrast, the positive PV200 anomalies are relatively smaller for westward-moving UTTs, and they are located in the tropical easterlies. This follows Igel et al (2021), where it is argued that TUTTs are advected by the background easterlies. Moreover, the boundary of westerly and easterly flow moves further north during westward-UTT events.…”
Section: Upper Troposphere Troughsmentioning
confidence: 88%
“…For the NAM region, tropical upper-troposphere troughs (TUTTs) are the most common IT type. TUTTs, unlike RWBs, are more common in subtropical easterlies, albeit they are also connected to mid-latitude wave breaking events (Igel et al, 2021). To assess their impact on precipitation, Finch and Johnson (2010b) utilized quasigeostrophic (QG) theory to study a TUTT event over the NAM region in July 2004.…”
Section: Upper Troposphere Troughsmentioning
confidence: 99%
“…In addition to near‐surface features, upper‐level disturbances were identified as influential controls on precipitation by Igel et al. (2021), who examined the impact of tropical upper troposphere troughs (TUTTs) on NAM precipitation, and Sierks et al. (2020), who highlighted the role of Rossby wave breaking (RWBs) and inverted troughs (ITs) over Lake Mead.…”
Section: Introductionmentioning
confidence: 99%
“…Frontal systems were found to be another significant driver associated with 44% of EPEs in the southwestern US summertime, as shown in Kunkel et al (2012). In addition to near-surface features, upper-level disturbances were identified as influential controls on precipitation by Igel et al (2021), who examined the impact of tropical upper troposphere troughs (TUTTs) on NAM precipitation, and Sierks et al (2020), who highlighted the role of Rossby wave breaking (RWBs) and inverted troughs (ITs) over Lake Mead. Beyond these synoptic features, Finch and Johnson (2010) and Mejia et al (2016) revealed the significance of mesoscale convection system (MCS) activities in the NAM region.…”
Section: Introductionmentioning
confidence: 99%